åˆ©ç”¨å¯¹æ¯”æ•™å¦æ³•æé«˜å¦ç”Ÿå¯¹â€œå°±â€ä¸Žâ€œæ‰â€çš„ç†è§£è¿ç”¨èƒ½åŠ› - Lius, .; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
æ‘˜è¦ ï¼šå‰¯è¯æ˜¯æ—¥å¸¸ç”Ÿæ´»äº¤é™…ä¸é€šå¸¸ç”¨çš„è¯ç±»ä¹‹ä¸€ï¼Œåœ¨æ±‰è¯ä¸å¸¸ç”¨çš„ å‰¯è¯â€œå°±â€ä¸Žâ€œæ‰â€ï¼Œè¿™ä¸¤è¯è¯ç”¨æ³•å¤šæ ·ï¼Œè¡¨è¾¾æ„ä¹‰ä¸åŒï¼Œæœ‰ä¸€å®šçš„åŒºåˆ«ã€‚å¯¹æ±‰è¯ä½œä¸ºç¬¬äºŒè¯è¨€çš„å¦ç”Ÿæ¥è¯´ï¼Œå¦ä¹ å‰¯è¯â€œå°±â€ä¸Žâ€œæ‰â€çš„ æ—¶å€™æœ‰ä¸€å®šçš„å›°éš¾ï¼Œå¾€å¾€å¦ç”Ÿä¼šè¯¯ç”¨ã€‚å› æ¤ï¼Œå‰¯è¯ä¹Ÿæˆä¸ºå¯¹å¤–æ±‰è¯ è¯æ³•çš„æ•™å¦é‡ç‚¹ã€‚ç¬”è€…åˆ©ç”¨å¯¹æ¯”æ•™å¦æ³•å¯¹å¤ä¸é«˜ä¸äºŒå¹´çº§XIæ–‡ç§‘1çå’ŒXIæ–‡ç§‘3çè¿›è¡Œâ€œå°±â€ä¸Žâ€œæ‰â€çš„æ•™å¦ã€‚ç›®çš„å°±æ˜¯é€šè¿‡å¯¹æ¯”æ•™å¦æ³•æ¥æé«˜å¦ç”Ÿå¯¹â€œå°±â€ä¸Žâ€œæ‰â€çš„ç†è§£å’ŒæŽŒæ¡ï¼Œå’Œä½¿ç”¨æµ‹è¯•æ³•æ¥äº†è§£ å¦ç”Ÿå¦ä¹ å‰å’Œå¦ä¹ åŽçš„æƒ…å†µå’Œç»“æžœï¼Œä»¥è¿›è¡Œå¯¹æ¯”ã€‚ç»“æžœå¾ˆæ˜Žæ˜¾ï¼Œå¦ä¹ åŽçš„æˆç»©æ¯”å¦ä¹ å‰æœ‰æ‰€æé«˜ï¼Œè¿™è¡¨ç¤ºå¯¹æ¯”æ•™å¦æ³•é€‚åˆç”¨äºŽè¿›è¡Œâ€œå°±â€ ä¸Žâ€œæ‰â€çš„æ•™å¦ã€‚ å…³é”®è¯ï¼šå‰¯è¯â€œå°±â€ä¸Žâ€œæ‰â€ï¼›å¯¹æ¯”æ•™å¦æ³• Abstract: Adverb is a part of speech that is often used in our daily life. In Chinese , adverb that often used is â€œjiuâ€ and â€œcaiâ€, these two words have different function and have prominent differences such as different in meaning . The learners who study Chinese as a second language, will face these difficulties during learning adverb of â€œjiuâ€ and â€œcaiâ€ .There are some erros in using these adverbs.Â Therefore, adverb has become the most important part in teaching Chinese grammar. The writer used the comparative teaching method to teach adverbs â€œjiuâ€ and â€œcaiâ€ for the Eleventh Grade Class 1 and class 3 students of Social Science of Santu Petrus Senior High School. The purpose is to improve students comprehensive Â mastery of the adverb â€œjiuâ€ and â€œcaiâ€ . In addition, test method was used to find out the studentsâ€™ studying condition and to compare their pre-test and post-test result.Â The results are significant, studentsâ€™ score after learning the material are higher than before learning the material. It means comparison method is suitable for teaching adverbs â€œjiuâ€ and â€œcaiâ€. Keywords: Adverbs â€œjiuâ€ and â€œcaiâ€; Comparative Teaching Method